Basic and application of system reference derivation in electroencephalography - MUNEKATA, Shinichi; SUZUKI, Junko; ONOZAWA, Yuya; KANOH, Yuhsaku (Japanese Journal of Medical Technology, 2019)
Accurate knowledge of the “system reference” is required to record the electrical activity of the brain by digital electroencephalography. The system reference exists in only digital electroencephalography and must be used. The original data of each electrode unit are obtained by preserving the potential difference between the system reference and each electrode. By using the original data to calculate, one can draw the electroencephalogram of each montage. In addition, it is difficult to detect the failure of the differential amplifier by the monopolar reference derivation; therefore, it is necessary to record the system reference derivation in each patient.